SOCIO-ECONOMIC IMPACT OF MULTIPLE LAND CERTIFICATE DISPUTES ON COMMUNITIES - Ikhwan, Muhammad; Widjaja, Gunawan (Penerbit Lafadz Jaya, 2025)
This study aims to analyse the social and economic impacts of multiple land title disputes on communities. Multiple land title disputes often occur due to discrepancies in the land administration system, leading to overlapping land ownership. This study reveals that the social impacts of multiple land title disputes are significant, including increased conflict between residents, deterioration of social relations, and decreased trust in government institutions. The economic impacts are also significant, with communities facing high legal costs and lost economic potential due to land that cannot be utilised productively. The research suggests the need for reforms in the land administration and agrarian justice systems, as well as increased legal awareness among communities to prevent and reduce multiple land disputes in the future. With these measures, it is hoped that social stability and economic recovery can be achieved, so that people can live more prosperously and harmoniously.